Persepsi Pemustaka terhadap Kualitas Pelayanan Sirkulasi Di Kantor Perpustakaan dan Arsip Kota Batam - Muharama, Safira Taris (Jurnal Administrasi Publik, 2015)
Abstract: User’s Perception Towards Service Quality of Libaries and Archive Office Circulation in Batam. The purpose of this study was to determine user’s perception towards circulation of library and archive office in Batam. The study used a purposive sampling method. Samples were taken from visitor’s who have already joined as a member of the libraries. The variables in this study is only one, there is User’s perceptionstowards service quality of libraries and archive office circulation in Batam. The analysis on the perception is based on five service quality dimensions: reliability, assurance, responsiveness, empathy and tangibles. The results showed that User’s perceptions towards service quality of libraries and archive office circulation in Batam is excellent. As the average value is 3.30, the interpretation is excellent. Keywords: User’s Perception, Service Quality, Circulation Service, Libraries Circulation Abstrak: Hasil penelitian yang didapat menunjukkan bahwa persepsi sebagian besar pemustaka terhadap kualitas pelayanan sirkulasi di Kantor Perpustakaan dan Arsip Kota Batam dengan total nilai rata-rata 3.30, dengan nilai grand mean masing-masing variabel XI:Kehandalan (Reliability) adalah 3.78, X2:Jaminan (Assurance) adalah 3.29, X3: Daya tanggap (Reponsiveness) adalah 3.09, X4:Empati (Empathy) adalah 3.05 dan X5:Bukti langsung (Tangibles) adalah 3.25 sehingga penafsiran/interpretasi kualitas pelayanan sirkulasinya tergolong sangat baik dan layak untuk digunakan oleh pemustakanya. Hal tersebut membuktikan bahwasannya ternyata bantuan teknologi IT tidak mempengaruhi persepsi buruknya pelayanan sirkulasinya. Kata Kunci: Persepsi Pemustaka, Kualitas Pelayanan, Pelayanan Sirkulasi, Sirkulasi Perpustakaan